"Their Today Is Our Future": Direct Carers' Work Experience and Formal Caring Relationships in a Community-Based Eldercare Program in Shanghai. (April 2018) - Chen, Lin; Ye, Minzhi; Kahana, Eva
The purpose of this study is to explore direct carers' work experience and formal caring relationships with older adults in a community-based eldercare program in Shanghai. Existing evidence has primarily focused on direct carers' work experience in residential care settings. However, direct carers' experiences of caring older adults in the community also deserve exploration. This qualitative study purposively sampled direct carers who worked in government-sponsored programs. Carers participated in semi-structured, in-depth interviews ( N = 37). Results reveal that despite occasional frustration, direct carers undertook demanding workloads and fostered strong emotional attachments with older adult clients. "Karma" was a critical cultural factor pertaining to their work ethic and motivated their care provision to benefit their future elderly selves. This study recognizes the cultural aspects of caring relationships that contribute to the quality of care of the community-based older adults in urban China.